Virtualization Technology for Optimizing Server Resource Usage - Edwar Ali; Didik Sudyana (International Conference on Engineering and Technology Development (ICETD), 2014)
Data and information needs for large organizations rely heavily on information technology infrastructure support. One of the necessary supporting components is the availability of a sufficient number of servers to increase data center. The huge costs required to increase the number of server units. Virtualization technology can be the perfect solution to resolve these problems. However, due to the high cost of a license, causing an open source-based virtualization used as the main option, namely Proxmox. The application virtualization based Proxmox, can maximize the use of resources, because the function of 3 units of physical servers can be enabled simultaneously on 1 physical server unit. The presence of live migration feature of Proxmox, allowing to move a virtual machine from one physical server to another physical server when maintenance underway. This change can take place without stopping services running on virtual machine.